Laparoscopic and robotic hepatectomy in living liver donors. Current state and prospects - K. O. Semash (Вестник трансплантологии и искусственных органов)
Minimally invasive living-donor hepatectomy is a relatively new surgical technique that can improve donor safety and expedite donor rehabilitation. Following an early stage of research where donor safety was not adequately established, the minimally invasive approach nowadays yields better outcomes when carried out by experienced surgeons. Important factors include donor selection criteria, hospital equipment, and surgeon’s learning curve. This review describes the current status of laparoscopic and robotic living-donor hepatectomy, along with the challenges facing the advancement of these surgical techniques.